DIALEKTOLOGI BAHASA BIAK - Yohanis Sanjoko; nfn Suharyanto; Eli Marawuri (Metalingua: Jurnal Penelitian Bahasa, 2016)
BIAK language is genetically one of West Papua New Guinea family, a sub-groupof language cluster of the Austronesia, Austronesian-Melayu Polinesian-CentralEastern-Eastern Melayu-Polinesian-South Halmahera-West New Guinea-West NewGuinea-Cenderawasih Bay-Biak. This paper discusses the Biak language fromthe dialectology perspective. The purpose of this paper is to describe the distinctiveelements of language contained in the Biak language variants, particularly atthe level of phonological and lexical; to describe the spreading pattern of thelinguistic elements differences; and to determine the status of each variantcontained in Biak language as well as its usage boundaries. Determination ofthe status of a variant to the level of language, dialect, subdialect, or differentspeech was done by a quantitative approach using dialectometry method. Theanalysis of the data uses both intralingual match method and extralingual matchmethod. The results shows that the Biak language is divided into six variantswhich each of them stands as subdialect. Biak language variants show differencesat the level of phonology and lexical. AbstrakBAHASA Biak adalah salah satu kelompok bahasa yang secara genetis termasuk dalamkerabat keluarga bahasa West Papua New Guinea, subgrup rumpun bahasa Austronesia,Austronesian-Melayu Polinesian-Central Eastern-Eastern Melayu-Polinesian-SouthHalmahera-West New Guinea-West New Guine-Cenderawasih Bay-Biak. Tulisan inimembahas bahasa Biak berdasarkan tinjauan dialektologi. Tujuan tulisan ini adalahuntuk mendeskripsikan perbedaan unsur-unsur kebahasaan yang terdapat di dalamvarian-varian bahasa Biak, terutama pada tataran fonologi dan leksikal; mendeskripsikanpola penyebaran perbedaan unsur-unsur kebahasaan tersebut; dan menentukan statustiap-tiap varian yang terdapat dalam bahasa Biak serta batas-batas wilayah pakainya.Penentuan status sebuah varian ke dalam tingkatan bahasa, dialek, subdialek, ataubeda wicara dilakukan dengan pendekatan kuantitatif. Pendekatan kuantitatifdilaksanakan dengan metode dialektometri. Analisis data penelitian ini menggunakanmetode padan intralingual (PI) dan metode padan ekstralingual (PE). Hasil pembahasanmenunjukkan bahwa bahasa Biak terbagi ke dalam enam varian dan keenamnyaberstatus sebagai subdialek. Pada tataran fonologi dan leksikal varian-varian bahasaBiak memperlihatkan perbedaan.